Black Women at War: A Comprehensive Framework for Research on the Strong Black Woman. Issue 3 (3rd July 2021) - Davis, Shardé M.; Jones, Martinque K.
Abstract: The "strong Black woman" image has historically served as a justification for Black women's oppression. While the image persists as a measure of control, it also serves as a powerful agent for Black women's survival in an oppressive world. The seemingly contradictory nature of this image has put scholars in a position to shift the framing of strength to consider its functionality. As a point of intervention, this conceptual review advances a comprehensive framework that articulates the ever-shifting functions of strength based upon 30 years of prior research. It employs war imagery, likening strength to facets of combat, to organize these ideas into a perspicuous heuristic. Advancing a new, comprehensive framework on strength will help scholars more fully understand the functionality of strength and the vital roles it plays in Black women's lives. The implications of this framework for scholars, practitioners, Black women, and allies are discussed.